Qaraqalpaqstan Respublikası miynet resurslarınıń qáliplesiwine demografiyalıq faktorlar hám xalıq migraciyasınıń tásiri - Auezov, Omirbay Tazabaevich (SCIENCE and SOCIETY, 2026)
The article examines the impact of demographic factors and population migration on the formation of labor resources in the Republic of Karakalpakstan. It also studies migration processes in the cities and districts of the Republic of Karakalpakstan.
Keywords: labor resources; migration movement; emigration; immigration; re-emigration; external migration; internal migration